Investigation of carbon capture and organic transformation mechanisms in advanced primary wastewater treatment system - Trisno, Elmer Augustinus (2019)
High Rate Activated Sludge (HRAS) system was widely developed for A-stage process. HRAS employs biosorption capability of activated sludge to improve organic removal performance of the primary treatment system. To the best of author’s knowledge, researchers rarely conducted studies on HRAS utilizing industrial-scale pilot plant and its performance operating under both aerobic and anaerobic condition. In addition, it has been observed in Ulu Pandan Integrated Validation Plant (IVP) that there is no significant difference for organic removal efficiency between HRAS system (60%) and conventional primary treatment process (55%). The objective of this study is to investigate carbon capture and organic transformation mechanisms in HRAS to deduce the reason behind the similarity of removal efficiency in both primary treatment system. Comparative analysis on carbon, nitrogen and phosphorus compound found in wastewater samples from both treatment train were conducted to evaluate organics and nutrient removal mechanisms, as well as carbon transformation mechanisms in the HRAS. Preliminary analysis on transformation mechanisms was further evaluated through simulating biosorption process in laboratory scale reactors under 3 different test conditions. Similarly, the comparative study on biodegradability characteristics of waste activated sludge helps in identifying the occurrence of organic transformation in the biosorption process. Comparative analysis on carbon capture performance of both treatment train showed that lamella plates employed in primary clarifier tank are sufficient to achieve high particulates removal efficiency. The introduction of biosorption treatment unit was found to slightly enhance the removal of colloidal and soluble carbon, as well as nitrogen compound in the wastewater. Operating the biosorption reactor under aerobic condition improved the removal efficiency of soluble organics and quality of primary effluent. The results from LC-OCD-OND analysis, anaerobic batch tests, and comparative study on biodegradability characteristics of primary sludges conclude that hydrolytic acidification is the prevailing reaction mechanisms for solubilization of particulates and colloidal organic compound in the biosorption reactor. Anaerobic batch experiments also demonstrated the benefits of the pre-treatment process in improving the biosorption capacity of reactor sludge. Insights from this project will provide a preliminary source of information in improving the design of constructing future WWTP and contribute towards the development of anaerobic biosorption system that is currently found to be lacking in the research community.